The Role of the Outstanding Professor Leopold Kasper in the Development of European Clinical Urology of the Second Half of the XIX and Early XX Centuries (to the 160th anniversary of his birth) - T. Sh. Morgoshiia (Вестник урологии)
The development and scientific priorities of European urology of the second half of the XIX and early XX centuries are analyzed. The main dates of life and scientific and practical activity of Prof. Leopold Kasper are presented. The scientific views and thoughts of the scientist are noted. He specialized in urology under the leadership of G. Thompson, P. Freyer, F. Guyon, I. Albarran and L. Dittel after graduating from the University of Berlin in 1883. L. Kasper was the founder of a large German urological school. In addition, he is the author of many works, among which research on cystoscopy, endoscopic operations, functional diagnosis of kidneys diseases, treatment of renal tuberculosis and kidney stone disease, prostate diseases, transurethral galvanocaustics of bladder tumors, etc. are particularly distinguished. He constructed a special catheterization cystoscope (1895) through which for the first time it became possible to study the functional ability of each kidney individually, which greatly facilitated the recognition and treatment of surgical diseases of the kidneys and upper urinary tract. He improved and put into practice a functional renal test with floridzine and cryoscopic urine examination obtained from each kidney separately by catheterization of the ureters. It is noted that L. Kasper was one of the founders of the Society of German urologists, whose founding meeting was held in 1907 in Vienna. In the same year, L. Kasper, together with other prominent surgeons and urologists, founded the journal «Zeitschrift für Urologie», of which he was editor for decades. L. Kasper was an honorary member of nineteen scientific societies, including the Society of Moscow urologists, of which he was elected an honorary member in 1924.